Using Video Technology to Improve Oral Presentation Skills among Undergraduate Students: A Systematic Literature Review - Nadjwa Miskam, Nuraqilah; Saidalvi, Aminabibi (International Journal of Psychosocial Rehabilitation, 2020)
Video technology has become one of the latest technologies being adopted in teaching oral presentation skills. However, there is a lack of an overview concerning the effects of video technology on undergraduate students’ oral presentation skills. To address the gap, this paper presented results of a systematic review of studies related to the use of video technology in learning oral presentation skills among undergraduates published from 2009 to 2019. The study synthesizes the trends on the use of video technology tools to improve students’ oral presentation skills. 15 related studies were identified using a systematic review of the Scopus and Web of Science databases guided by the PRISMA Statement (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The findings pointed out the effects of using video technology in improving students’ oral presentation skills in terms of the content, fluency, pronunciation, vocabulary, and organization. The findings also highlighted the students’ perception and challenges in using video technology to improve their oral presentation skills. It can be concluded that video technology is an effective tool in improving students’ oral presentation skills. This study still has room for improvement by narrowing the scope of review as the future direction for the research of video technology in oral presentation and to practice different techniques of searching, such as snowballing, citation tracking, and reference searching.